2010
DOI: 10.1017/s0022215110001908
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of vestibular evoked myogenic potentials elicited by click and short duration tone burst stimuli

Abstract: The latency of the vestibular evoked myogenic potential responses (i.e. the p13 and n23 peaks) was longer for tone burst stimuli compared with click stimuli. The amplitude of the p13-n23 waveform was greater for tone burst stimuli than click stimuli. Thus, the click stimulus may be preferable for clinical assessment and identification of abnormalities as this stimulus has less variability, while a low frequency tone burst stimulus may be preferable when assessing the presence or absence of vestibular evoked my… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
12
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 17 publications
2
12
0
Order By: Relevance
“…Peak-peak amplitude was significantly high for 500 Hz short duration tone burst when compared with click stimuli. Similar findings have been reported by [9, 11] using cVEMP response. …”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Peak-peak amplitude was significantly high for 500 Hz short duration tone burst when compared with click stimuli. Similar findings have been reported by [9, 11] using cVEMP response. …”
Section: Discussionsupporting
confidence: 92%
“…Larger VEMP amplitudes with 500 Hz tone bursts than with 1000 Hz and 2000 Hz tone bursts were observed [10]. Short latency was observed for click evoked cVEMP as compared to short duration tone burst stimuli [9, 11]. These authors reported a higher response rate for the click stimuli than the short duration tone burst stimuli.…”
Section: Introductionmentioning
confidence: 99%
“…The non-inverting electrode was placed at the midpoint of the SCM of the side being evaluated and the inverting electrode was the sternoclavicular junction, with the forehead serving as the site for the ground electrode. The stimulus utlised for recording cVEMP was 500 Hz tone burst stimulus (2 msec rise time, 2 msec fall time, 0 msec plateau time, Blackmann window) as 500 Hz tone burst stimulus gives better amplitude compared to the click stimulus [17]. The responses were filtered from 30 Hz to 1500 Hz.…”
Section: Cervical Vestibular-evoked Myo Genic Potentials (Cvemps)mentioning
confidence: 99%
“…STBs of 500 Hz have been reported to evoke more robust and clear cVEMP responses compared to clicks as well as 1 and 2 kHz STBs [25]. However, paradoxical and uncomplimentary findings have also been reported wherein clicks were reported to produce earlier latencies of the individual peaks though not larger amplitudes of cVEMP [11]. The differences in the findings might well be attributed to use of different rise/fall and plateau times by the two set of authors.…”
Section: Introductionmentioning
confidence: 99%
“…The differences in the findings might well be attributed to use of different rise/fall and plateau times by the two set of authors. Murofushi et al [25] used 1 ms rise/fall time and 2 ms plateau time where as Kumar et al [11] used 2 ms rise/fall time ramped through a Blackman's window which implies a plateau time of 0 ms. These differences in the stimulus rise/fall and plateau times might probably have resulted in the differences between the findings of the two studies.…”
Section: Introductionmentioning
confidence: 99%